2003
DOI: 10.1073/pnas.2237238100
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of hepatitis C virus RNA replication through inhibition of host protein geranylgeranylation

Abstract: Hepatitis C virus (HCV) RNA replication depends on viral protein association with intracellular membranes, but the influence of membrane composition on viral replication is unclear. We report that HCV RNA replication and assembly of the viral replication complex require geranylgeranylation of one or more host proteins. In cultured hepatoma cells, HCV RNA replication was disrupted by treatment with lovastatin, an inhibitor of 3-hydroxy-3-methyglutaryl CoA reductase, or with an inhibitor of protein geranylgerany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
326
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(344 citation statements)
references
References 31 publications
16
326
0
2
Order By: Relevance
“…The availability of fewer lipid rafts for replication seems to be a plausible explanation for at least some of the anti-HCV properties of statins. 32,33 The well-studied anti-inflammatory and immunomodulatory effects of statins with respect to cardiovascular and other organ systems may also explain the beneficial effects observed here in conjunction with PEG-IFN and RBV therapy. Peroxisome proliferatoractivated receptor alpha (PPAR-a) is a nuclear hormone receptor important in regulating lipid, cholesterol, carbohydrate, and steroid metabolism in the liver as well as the kidneys, heart, and skeletal muscle.…”
Section: Discussionmentioning
confidence: 80%
“…The availability of fewer lipid rafts for replication seems to be a plausible explanation for at least some of the anti-HCV properties of statins. 32,33 The well-studied anti-inflammatory and immunomodulatory effects of statins with respect to cardiovascular and other organ systems may also explain the beneficial effects observed here in conjunction with PEG-IFN and RBV therapy. Peroxisome proliferatoractivated receptor alpha (PPAR-a) is a nuclear hormone receptor important in regulating lipid, cholesterol, carbohydrate, and steroid metabolism in the liver as well as the kidneys, heart, and skeletal muscle.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, by demonstrating no genotype or SVR-related differences in lanosterol levels, we controlled for any potential differences preceding this step in the presqualene mevalonate pathway. We were consequently unable to address the role of the earlier isoprenoid pathway steps and processes (such as geranylgeranylation 14,38 ) that have been associated with viral replication, or alternative isoprenoid pathway products (such as prostaglandin and arachidonic acid). Importantly, however, we were able to address the late steps of cholesterol synthesis with a high degree of specificity, irrespective of possible earlier HCV interference in the sterol pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that membrane fluidity is important for the function of the membranous web. In addition, two groups have shown that inhibition of protein geranylgeranylation leads to the disassembly of HCV replication complexes and strong inhibition of HCV RNA replication 69,70 . In the absence of appropriate prenylation motifs in HCV proteins, these results suggest that a geranylgeranylated cellular protein participates in HCV replication and could be amenable to pharmacological manipulation.…”
Section: Mechanisms Of Hcv Rna Replicationmentioning
confidence: 99%